A new outstanding species and a new section of Dalea (Fabaceae: Papilionoideae) from central Mexico - Castillón, Eduardo Estrada; Martínez-Ramírez, Julio; Mares-Guerrero, Andrés Alejandro; Ocampo, Gilberto (Phytotaxa, 2020)
We describe and illustrate Dalea rubriflora A.E. Estrada, J. Martínez-Ramírez, A. Mares & Ocampo as a new species from central Mexico. According to the morphology of its flower, this new species is included in a new section within subgenus Parosela because the shape of its keel, the innermost petals (which make the flower valvate) coherent along their external (dorsal) outer margins. However, this new species and new section have striking differences with the rest of the previously described taxa of subgenus Parosela, highlighting 1) the persistent red color of the flowers, not found in any section and species of Dalea, 2) the stamens are joined in a very long staminal column which are protruded from the keel petals for almost a third of its length, and 3) the blades of the epistemonous petals are not auriculated, instead, are truncated in the keel and absent in the wings. These main features, associated with more particular characteristics of other sections, allow us to recognize Rubriflorae as a new section and Dalea rubriflora as a new species into the subgenus Parosela.